Decree-Law of the President of the Arab Republic of Egypt No. 164 of the Year 2013 On Amending Some Provisions of the Income Tax Law Promulgated by Law No. 91 of the Year 2005 = قرار رئيس جمهورية مصر العربية بالقانون رقم 164 لسنة 2013 بتعديل بعض أحكام قانون الضريبة على الدخل الصادر بالقانون رقم 91 لسنة 2005 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.